Unhei’s Adaptation as an Asian American Immigrant Child in The Name Jar by Yangsook Choi - Amanda Nur Syafika; Yosep B. Margono Slamet (International Journal of Multilingual Education and Applied Linguistics, 2026)
Immigrant children often face challenges in adjusting and adapting to new environments. This study analyses the adaptation process of the main character, Unhei, as an Asian American immigrant child in Yangsook Choi’s picture book The Name Jar. This study examines the challenges Unhei faces in The Name Jar as she attempts to adapt and maintain her identity in a new environment in America, including language barriers, cultural differences, and social interactions with peers. This study employs a qualitative method using text and illustration analysis based on the adaptation theory proposed by Lamme et al. (2004), which consists of three stages: making transitions, making connections, and becoming American. The findings show that Unhei experiences various challenges in adapting to her new environment, including language barriers, cultural differences, and difficulties in social interaction. Unhei undergoes three stages of adaptation; making transitions, making connections, and becoming American. In the making transitions stage, Unhei experiences confusion, insecurity, and difficulty adjusting to a new cultural and social environment. In the making connections stage, she maintains connections with her Korean identity through her family, language, traditional objects, and Korean food while gradually building relationships in her new environment. In the becoming American stage, Unhei begins to adapt to American society and develops confidence in accepting her Korean identity without abandoning her cultural background. Furthermore, Unhei’s experience reflects that adaptation does not always occur smoothly, but involves a process of self-negotiation in dealing with cultural differences. The adaptation process is dynamic and influenced by both internal and external factors, and positive social interactions can help accelerate successful adaptation in a new environment.